2020
DOI: 10.3389/fpubh.2020.00514
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Video Visits During COVID-19: Lessons Learned From a Primary Care Practice in New York City

Abstract: Background: During the height of the coronavirus (COVID-19) pandemic, there was an unprecedented demand for "virtual visits," or ambulatory visits conducted via video interface, in order to decrease the risk of transmission. Objective: To describe the implementation and evaluation of a video visit program at a large, academic primary care practice in New York, NY, the epicenter of the COVID-19 pandemic. Design and participants: We included consecutive adults (age > 18) scheduled for video visits from March 16,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 19 publications
(18 reference statements)
2
44
1
5
Order By: Relevance
“…This indicates that more seamless integration of VCs with GPs’ electronic record systems still remains a priority. Despite some technical challenges, the GPs reported that 85% of the patients seemed satisfied with the VCs, in accordance with existing knowledge on patient experience with VCs [ 9 , 37 , 38 ]. In about half the consultations, the GPs in our survey also deemed it realistic to handle a similar issue by VC in a future, normalized situation.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This indicates that more seamless integration of VCs with GPs’ electronic record systems still remains a priority. Despite some technical challenges, the GPs reported that 85% of the patients seemed satisfied with the VCs, in accordance with existing knowledge on patient experience with VCs [ 9 , 37 , 38 ]. In about half the consultations, the GPs in our survey also deemed it realistic to handle a similar issue by VC in a future, normalized situation.…”
Section: Discussionsupporting
confidence: 77%
“…In our study, GPs experienced technical difficulties in 10% of the consultations, somewhat less than a comparable study performed in New York City in March 2020, where technical problems were reported in 13% of consultations [ 37 ]. This indicates that more seamless integration of VCs with GPs’ electronic record systems still remains a priority.…”
Section: Discussioncontrasting
confidence: 66%
“…Such a framework would imbibe resilience, innovationdriven technology, and scaled intelligence to enable systems to evolve and be responsive to local and emergent needs such as during an outbreak. COVID-19 has led to a sharp increase in the demand for telemedicine services (5,34). It also has an impact on telemedicine providers, a sector that is facing unprecedented demand, which by some estimates has grown by 150% or more (66).…”
Section: Discussionmentioning
confidence: 99%
“…Quarantined doctors can provide these services in medical institutions with remote access or care via telecommunications directly to the consumer, freeing other doctors to provide immediate assistance to more needy patients. Teleconsultations allow doctors to evaluate patients, detect signs of infection, and quickly and easily document patients who might be at higher risk of illness (34). Telemedicine solutions work promptly, filling out insurance documents, which allows doctors to devote more time to treating patients.…”
Section: Artificial Intelligence Assisted Telemedicinementioning
confidence: 99%
“…Using program data, surveys, and informal interviews, this model was found to be feasible and acceptable for supporting patients from socioeconomically vulnerable populations during self-isolation and quarantine. In another example, New York City primary care facilities developed processes to guide patients through a video-delivered primary care practice appointment ( 20 ). The team applied RE-AIM and found significant differences in terms of reach and representativeness (i.e., patients were more likely to be younger adults, women, and have commercial insurance).…”
Section: Providing Structure During the Covid-19 Pandemicmentioning
confidence: 99%